Slovene Language and the Law on Higher Education – We Wish to Continue the Proud Legacy of Pleteršnik’s Great and Outstanding Slovene - Jesenšek, Marko (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
Pleteršnik’s Slovene-German Dictionary accumulates the best Slovene lexicogra-phy could offer, adding also numerous manuscript collections and systematically gathered material from the Slovene language of the19th century. This resulted in the creation of the best existing dictionary of the Slovene language, containing also a contemporary phonological theory and the foundations for a Slovene handbook of orthography. Indeed, it also demonstrates Pleteršnik’s attitude towards language in general – it defends Slovene as the language of instruction and at the same time as a language which by contrast is used for the understanding of numerous foreign languages. Pleteršnik’s view of the mother tongue is currently confronted with the effort to amend the Law on Higher Education demonstrated in the senseless desire for English to become the language of instruction at Slovene universities.